The Effect of Social Support on Single Mothers’ Subjective Well-Being and Its Implication for Counseling - Muarifah, Alif; Widyastuti, Dian Ari; Fajarwati, Indah (Jurnal Kajian Bimbingan dan Konseling, 2019)
The present study aimed to discover the effect of social support on single mothers’ subjective well-being. This study employed a correlational approach. One hundred fifty nine single-mothers in Bantul regency, Special Region of Yogyakarta, Indonesia were involved in this study, determined using quota sampling. The data were collected using social support and subjective well-being scales. Simple linear regression was used to analyze the data. The present study exhibited that social support significantly affects single mothers’ subjective well-being. This study can be used as a reference proving that social support is much needed by a single-mother to obtain subjective well-being. Therefore, a service in the form of a psychoeducational group is required in the community to enhance social support on single-mother. It can also be in the form of psychoeducational group and counseling services for single-mother to enhance her subjective well-being.